A Study of the Parallels Between Visual Art and Music : the Big Misconception. - Jurečič, Bostjan (Cambridge Scholars Publisher, 2019)
Standard surveys of 20th century visual art imply that there is a continuity between, say, Rembrandt and Koons, between Caravaggio and Hirst. Even the sharp critics of artists who dominate the contemporary art scene, such as Warhol, Hirst, Ai Weiwei and countless others, imply such a continuity. They are all wrong. There is no such continuity, or, more precisely, it is only very weak, at best. This book explains why and how the claims regarding this continuity are false, and how we arrived at this point of great confusion about the arts.